2006
DOI: 10.21273/hortsci.41.7.1602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prohexadione-Ca and GA4+7 on Scarf Skin and Fruit Maturity in Apple

Abstract: Nutrient release characteristics of four different controlled-release fertilizers (Osmocote, Nutricote, Polyon, and Multicote) were monitored during an 11-month period in a simulated outdoor nursery production facility. Although no plants were used in the experiment, fertilization rates, irrigation regimes, and cultural practices simulated those typically used to produce fast-growing, high-nutrient-requiring containerized woody ornamentals. Fertilizer prill release characteristics were monitored through analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The effects of combining a single application of P-Ca at PF with three or four GA 4+7 sprays on russet were additive as determined by the lack of an interaction term in a factorial analysis of the data in the present experiments. This result is in agreement with previous studies on a different skin disorder of apple fruit (scarf skin), in which the combination of P-Ca with the first of three GA 4+7 sprays was more effective than either material alone (McArtney et al, 2006). These results are not consistent with the findings of Miller (1998), who reported that P-Ca sprays did not affect the activity of a GA 4+7 program for russet control on 'Golden Delicious' in two different experiments.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The effects of combining a single application of P-Ca at PF with three or four GA 4+7 sprays on russet were additive as determined by the lack of an interaction term in a factorial analysis of the data in the present experiments. This result is in agreement with previous studies on a different skin disorder of apple fruit (scarf skin), in which the combination of P-Ca with the first of three GA 4+7 sprays was more effective than either material alone (McArtney et al, 2006). These results are not consistent with the findings of Miller (1998), who reported that P-Ca sprays did not affect the activity of a GA 4+7 program for russet control on 'Golden Delicious' in two different experiments.…”
Section: Discussionsupporting
confidence: 93%
“…The main effect of P-Ca on mean fruit weight at harvest was neutral; however, P-Ca reduced fruit weight in three of the four experiments in the current study. In a previous study, we also found that P-Ca reduced mean fruit weight (McArtney et al, 2006). Because the effects of P-Ca on fruit set were only measured in one of the four experiments reported here, it is not known at this time if the fruit size response is a direct effect of the combined treatment on fruit growth or if it is mediated by a crop load effect.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In 2011, P-Ca alone reduced scarf skin by 7% compared with the untreated control (P = 0.0046); however, this effect was negated when combined with GA 4+7 + 6-BA. These data are consistent with other reports in the literature that found a reduction in scarf skin associated with GA 4+7 and P-Ca (McArtney et al 2006).…”
Section: Fruit Qualitysupporting
confidence: 93%